Development and characterization of polymer films of starch extracted from the jackfruit seed (Artocarpus Heterophilus) and polyvinylpyrrolidone for dressing (Research, Society and Development, 2022)
Burns represent a significant harm to public health, as they occur among the most varied degrees, often with extreme severity and risk of death, requiring a device that helps in the treatment of the damaged regions. Several biomaterials are evaluated for their effectiveness in the treatment of these lesions, being applied as curative films. Therefore, through the benefits of starch and Polyvinylpyrrolidone (PVP), this work aims to develop polymeric films based on starch extracted from jackfruit kernels with PVP, using the casting technique. The results obtained for the films showed the interaction between starch and PVP, showing good strength and elasticity, in addition to being within the thickness limits for use as a dressing. The addition of PVP considerably increased the percentage of swelling of the films, however, it reduced the thermal resistance of the material. Thus, films produced based on jackfruit starch with PVP presented physical and functional properties that make them favorable to be used in possible applications, such as dressings, for controlled release of drugs antimicrobials, exposing a low-cost renovation alternative, a since the dressings currently available on the market are too expensive.